Natural additives for reducing formaldehyde emissions in urea-formaldehyde resins - Luísa Carvalho (2015)
This work studies the use of soy protein as a natural formaldehyde scavenger in wood particleboard production. The protein is incorporated in two forms: a) as a powder, during the blending process of wood particles with urea-formaldehyde binder resin, and b) as an aqueous solution, added at different times during resin synthesis. Analysis of variance (ANOVA) was used to evaluate the signifi cance level of two effects (amount of added soy and time of addition) on internal bond strength, thickness swelling, and formaldehyde content of the resulting panels. The results showed that soy protein can contribute to decrease the formaldehyde content of particleboard panels. Addition in powder form or in solution during the resin condensation step leads to the highest formaldehyde reduction, without signifi cantly affecting the physical properties of the panels.